3D bioprinting technology to construct bone reconstruction research model and its feasibility evaluation - Lv, Xiao; Zhang, Chenyang; Liu, Xingzhu; Li, Ping; Yang, Yadong (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: To explore and construct a 3D bone remodeling research model displaying stability, repeatability, and precise simulation of the physiological and biochemical environment in vivo. Methods: In this study, 3D bioprinting was used to construct a bone reconstruction model. Sodium alginate (SA), hydroxyapatite (HA) and gelatin (Gel) were mixed into hydrogel as scaffold material. The osteoblast precursor cells MC3T3-E1 and osteoclast precursor cells RAW264.7 were used as seed cells, which may or may not be separated by polycarbonate membrane. The cytokines osteoprotegerin (OPG) and receptor activator of NF-κB ligand (RANKL) were used to induce cell differentiation. The function of scaffolds in the process of bone remodeling was analyzed by detecting the related markers of osteoblasts (alkaline phosphatase, ALP)and osteoclasts (tartrate resistant acid phosphatase, TRAP). Results: The scaffold showed good biocompatibility and low toxicity. The surface morphology aided cell adhesion and growth. The scaffold had optimum degradability, water absorption capacity and porosity, which are in line with the conditions of biological experiments. The effect of induced differentiation of cells was the best when cultured alone. After direct contact between the two types of cells at 2D or 3D level, the induced differentiation of cells was inhibited to varying degrees, although they still showed osteogenesis and osteoclast. After the cells were induced by indirect contact culture, the effect of induced differentiation improved when compared with direct contact culture, although it was still not as good as that of single culture. On the whole, the effect of inducing differentiation at 3D level was the same as that at 2D level, and its relative gene expression and enzyme activity were higher than that in the control group. Hence the scaffold used in this study could induce osteogenesis as well as osteoclast, thereby rendering it more effective in inducing new bone formation. Conclusion: This method can be used to construct the model of 3D bone remodeling mechanism.